Brassica rapa AGG 97809 BRAS ... - GLIS Of The ITPGRFA (Australian Grains Genebank, DEECA, 2023)
Plant Genetic Resource. Taxonomy: Brassica rapa Common name(s): Turnip Other names: MÅLSELVNEPE GIBOSTAD STAMME Conserved by: Australian Grains Genebank, DEECA (AGG), Australia Local sample unique identifier: AGG 97809 BRAS Method of creation: Acquisition Date: 2015-09-02 Historical: No Biological status: Other MLS status: Included ...